2018
DOI: 10.14710/jwl.6.2.100-114
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kelompok Masyarakat dalam Rehabilitasi Ekosistem Mangrove di Pesisir Kota Semarang

Abstract: The coastal area of Semarang City has a strategic function for regional economic development. Due to land use change, the environmental quality of coastal area is damaged and declining. The environmental quality decline has affected the socio-economic quality of local community. This research aims to investigate the role of local community in sustainable environmental management in Semarang City coastal area. The study takes place in two kelurahans, namely Tugurejo and Mangunharjo, and applies a descriptive qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
24

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 8 publications
(11 reference statements)
0
23
0
24
Order By: Relevance
“…The research result revealed that the diversity of mangrove species in Tapak was moderate because it was influenced by human intervention; for example, they planted mangroves for rehabilitation of this area. Therefore the types and numbers of mangroves found were not too diverse (Martuti et al, 2018). The richness index of the mangrove species found in Tapak was 0.999 (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…The research result revealed that the diversity of mangrove species in Tapak was moderate because it was influenced by human intervention; for example, they planted mangroves for rehabilitation of this area. Therefore the types and numbers of mangroves found were not too diverse (Martuti et al, 2018). The richness index of the mangrove species found in Tapak was 0.999 (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…In general, the existing land use in the research location is dominated by ponds with an area of 323.25 ha, where the farms cultivated in the area are fish and shrimp ponds. The extent of the pond area in the area is one of the causes of abrasion, this is due to the fact that most of the pond area that exists at present is a mangrove ecosystem (Martuti et al, 2018). Another large area of land use is rice fields with an area of 68.29 ha, where rice fields cultivated in the area are irrigated with a harvest time of 2 times a year.…”
Section: Results and Discussion 1 Coastal Region Of Tugurejo Subdistrictmentioning
confidence: 99%
“…Another large area of land use is rice fields with an area of 68.29 ha, where rice fields cultivated in the area are irrigated with a harvest time of 2 times a year. Furthermore, there is a mangrove ecosystem with an area of 28.79 ha, the mangrove in the study area has a spatial pattern that extends on the embankment of the pond and groups adjacent to the coast and airports, where most of the mangroves are on the edge of the pond resulting in very isolated growth of the plant which impacts on plant growth cannot be optimal (Martuti et al, 2018). The following table presents the distribution of land use at the research site.…”
Section: Results and Discussion 1 Coastal Region Of Tugurejo Subdistrictmentioning
confidence: 99%
See 2 more Smart Citations